2004
DOI: 10.1074/jbc.m406164200
|View full text |Cite
|
Sign up to set email alerts
|

The Venus Fly Trap Domain of the Extracellular Ca2+-sensing Receptor Is Required for l-Amino Acid Sensing

Abstract: We previously demonstrated that the human calciumsensing receptor (CaR) is allosterically activated by Lamino acids (Conigrave, A. D., Quinn, S. J., and Brown, E. M. (2000) Proc. Natl. Acad. Sci. U. S. A. 97, 4814 -4819). However, the domain-based location of amino acid binding has been uncertain. We now show that the Venus Fly Trap (VFT) domain of CaR, but none of its other major domains, is required for amino acid sensing. Several constructs were informative when expressed in HEK293 cells. First, the wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 20 publications
2
66
0
Order By: Relevance
“…CaR, similar to other class 3 family GPCRs that bind amino acids such as the metabotropic glutamate (mGluR 1 ) (23) and heterodimeric GABA B R (24) receptors, shares a functional Nterminal Venus Fly Trap domain. Unlike the mGluR 1 and GABA B R but similar to the taste receptor type 1 members 1 and 3 amino acid sensing taste receptor heterodimer (25) and the less well-characterized nutrient-sensing receptor, GPRC6A (26), CaR recognizes a broad array of L-amino acids interacting within the Venus Fly Trap domain (27). However, CaR has a preference for aromatic amino acids, such as Phe and Trp, in vitro in transfected HEK293 cells (11) and acutely isolated human parathyroid cells (14).…”
Section: Low Basal Gastrin and Absent Gastrin Response To Luminal Nutmentioning
confidence: 99%
See 1 more Smart Citation
“…CaR, similar to other class 3 family GPCRs that bind amino acids such as the metabotropic glutamate (mGluR 1 ) (23) and heterodimeric GABA B R (24) receptors, shares a functional Nterminal Venus Fly Trap domain. Unlike the mGluR 1 and GABA B R but similar to the taste receptor type 1 members 1 and 3 amino acid sensing taste receptor heterodimer (25) and the less well-characterized nutrient-sensing receptor, GPRC6A (26), CaR recognizes a broad array of L-amino acids interacting within the Venus Fly Trap domain (27). However, CaR has a preference for aromatic amino acids, such as Phe and Trp, in vitro in transfected HEK293 cells (11) and acutely isolated human parathyroid cells (14).…”
Section: Low Basal Gastrin and Absent Gastrin Response To Luminal Nutmentioning
confidence: 99%
“…This acid stimulatory effect of cinacalcet acting on both the G (42) and parietal cell (18) may warrant acid suppressive therapy to prevent cinacalcet intolerance caused by hyperacidity in vulnerable hemodialysis patients on long-term therapy for secondary hyperparathyroidism (43). The inhibition of gastrin secretion by NPS 2143 suggests that clinical trials of calcilytics for the treatment of osteoporosis should monitor potential deleterious inhibition of CaR on nonclassical Ca 2+ regulatory tissues (9,27,28).…”
Section: Deletion Of Car Does Not Significantly Alter the Gastrin Secmentioning
confidence: 99%
“…The CaSR binds and responds to various endogenous ligands including not only extracellular Ca 2+ (Ca 2+ o ) and Mg 2+ but also organic multivalent cations such as spermine, which acts as an allosteric agonist [8] and L-amino acids, which act as positive modulators (review: [9]) that bind in the receptor's VFT domain [10]. In addition, the CaSR is activated by synthetic modulators (calcimimetics) including the clinically effective phenylalkylamine cinacalcet, which bind in the receptor's heptahelical domain [11].…”
Section: Introductionmentioning
confidence: 99%
“…S1). The results indicate that ␥-glutamyl peptides and S-methylgluta- (14) and glutathione (21) binding sites to the VFT domain and we previously identified T145A/S170T as a double mutant form of the VFT domain with near-normal Ca 2ϩ o -sensitivity but markedly impaired L-amino acid sensing (15). In the current study, we first confirmed that this mutant exhibited normal or near-normal Ca 2ϩ o sensitivity in the absence of L-Phe or S-methylglutathione (Fig.…”
Section: Effects Of ␥-Glutamyl Peptides On Camentioning
confidence: 90%
“…1). Based on chimeric receptor and mutational analyses, L-amino acids bind in the receptor N-terminal Venus Fly Trap (VFT) domain (14) and the effects of L-amino acids are selectively impaired by a double mutant (T145A/S170T), which exhibits normal Ca 2ϩ o -sensing (15). Comparative molecular modeling of the mGlu-1 and CaR VFT domain ligand binding surfaces indicates that, whereas the amino acid side-chain binding region is tightly defined by a cluster of positively charged residues in mGlu-1 and other mGlus (16,17) it is relatively unrestricted in the CaR and closely related class C GPCRs including GPRC6A and T1R1 (18).…”
mentioning
confidence: 99%